Legal Protection for Notarists in The Providing of Working Capital Credit by Bank (Study of The Decision of Mahkamah Agung Number 65 K/Pdt/2020) - Vianney, Janice; Nurdin, Aad Rusyad (Faculty of Law, Universitas Pekalongan, 2024)
Banks are business entities that collect funds from the public in the form of credit or other forms in order to improve the standard of living of many people. Based on the Banking Law, credit is